An examination of financial well-being factors among youth SME in Sabah, Malaysia using the two-stage least squares method - Sarimah Surianshah; Ho, Chong Mun; Salmah Topimin (School of Quantitative Sciences (SQS) UUM College of Arts & Sciences Universiti Utara Malaysia, 2024)
Day by day, the incidence of financial distress among young people is on the rise. This study aims to examine the effects of financial literacy indicators on the financial well-being of youth that has been involved in Small and Medium Enterprises (SMEs). Data (N = 301) were collected via a face-to-face and online survey conducted in the low and midrange economic state of Malaysia, Sabah. Using the two-stage least squares method, our results suggest that financial management and saving literacy are associated with better financial well-being among youth in Sabah. These financial literacy factors’ effects, along with family and government support, were amplified when the potential endogeneity in the estimates model was addressed. Varying results were also found in the financial well-being model based on youth’s education and industries involvement in SME business in Malaysia. Applied implications for financial literacy enhancement are provided. Finally, a new policy-relevant framework for financial education among young people is drafted, which may contribute to the achievement of the Sustainable Development Goals (SDG-8, Decent Work and Economic Growth).